EFFECT OF STAINING ON THE ROUGHNESS OF BEECH FURNITURE SURFACES - Atanasova, Krasimira; Angelski, Dimitar (Innovation in Woodworking Industry and Engineering design, 2025)
Staining is a process of transparent wood surface colouring. Stains are liquid systems that wet and penetrate treated surfaces, changing their properties, including their roughness. The article presents research on the surface roughness change of beech, beech plywood, and beech veneered wood-fibre boards after treatment with waterborne and solvent-based stains and waterborne stains with PVA resin additive. Before staining, the surfaces were sanded with P150-grain sandpaper. A contact roughness tester model SJ-210 and a standard Gaussian filter were used to evaluate the roughness. The influence of the substrate structure, the stain dilution and the type of thinner on the surface roughness were determined. The parameters Ra, Rpk, Rk, Rvk and the composite parameter Rpk+Rk+Rvk were analysed. The results are presented graphically and also in tables.